Strategies for implementing an electronic patient-reported outcomes-based symptom management program across six cancer centers - Michael Hassett; Samira Dias; Christine Cronin; Deborah Schrag; Nadine McCleary; Jaclyn Simpson; Tiana Poirier-Shelton; Jessica Bian; James Reich; Don Dizon; Megan Begnoche; Hannah Hazard Jenkins; et al. (BMC, 2024)
Abstract Background Electronic patient-reported outcome (ePRO)-based symptom management improves cancer patients' outcomes. However, implementation of ePROs is challenging, requiring technical resources for integration into clinical systems, substantial buy-in from clinicians and patients, novel workflows to support between-visit symptom management, and institutional investment. Methods The SIMPRO Research Consortium developed eSyM, an electronic health record-integrated, ePRO-based symptom management program for medical oncology and surgery patients and deployed it at six cancer centers between August 2019 and April 2022 in a type II hybrid effectiveness-implementation cluster randomized stepped-wedge study. Sites documented implementation strategies monthly using REDCap, itemized them using the Expert Recommendations for Implementation Change (ERIC) list and mapped their target barriers using the Consolidated Framework for Implementation Research (CFIR) to inform eSyM program enhancement, facilitate inter-consortium knowledge sharing and guide future deployment efforts. Results We documented 226 implementation strategies: 35 'foundational' strategies were applied consortium-wide by the coordinating center and 191 other strategies were developed by individual sites. We consolidated these 191 site-developed strategies into 64 unique strategies (i.e., removed duplicates) and classified the remainder as either 'universal', consistently used by multiple sites (N = 29), or 'adaptive', used only by individual sites (N = 35). Universal strategies were perceived as having the highest impact; they addressed eSyM clinical preparation, training, engagement of patients/clinicians, and program evaluation. Across all documented SIMPRO strategies, 44 of the 73 ERIC strategies were addressed and all 5 CFIR barriers were addressed. Conclusion Methodical collection of theory-based implementation strategies fostered the identification of universal, high-impact strategies that facilitated adoption of a novel care-delivery intervention by patients, clinicians, and institutions. Attention to the high-impact strategies identified in this project could support implementation of ePROs as a component of routine cancer care at other institutions. Trial registration ClinicalTrials.gov. NCT03850912. February 22, 2019. https://clinicaltrials.gov/ct2/show/NCT03850912?term=hassett&draw=2&rank=1